Installation of floor tiles finishes / Muhammad Aiman Haziq Ahmad Rizal - Ahmad Rizal, Muhammad Aiman Haziq (Universiti Teknologi MARA, ,Perak, 2021)
A tile is a type of decorative and functional wall or floor material that's commonly used to cover various interior surfaces. They are mainly made up of clay or any other type of material. These materials are also made from recycled content. The process of making tiles involves various steps, such as extrusion, pressing, and fire. After the tiles have been molded, they are subjected to fire to obtain the desired properties. Different types of tiles used in building construction are available in glazed or unglazed form.